THE ROLE OF RAMAN SPECTROMETRY IN DETERMINING THE SENSITIVITY OF THE CAUSES OF CHRONIC TONZILLITIS - E. S. Burenkov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Purpose of work. To study the sensitivity of pathogens of chronic tonsillitis to the combination of antibiotics amoxicillin + clavulanic acid using Raman spectroscopy. Materials and methods. The study involved 117 patients (all men) in the period of exacerbation of chronic tonsillitis, who were prescribed amoxicillin  / clavulanic acid for its relief according to the standard scheme.  Determination of the sensitivity of the microflora of the tonsils was carried out using the method of Raman spectroscopy. The principle of the method was to determine the irradiation of microflora in samples under the action of an antibiotic by the presence of products of microbial metabolism in it. Results. Clinical analysis of the results of the treatment in this group of patients showed that 96 of them (82 %) had a quick clinical effect. In 13 patients (11.1 %), it was necessary to increase the duration of taking the antibiotic by an average of 3-5 days, and in 8 patients, to eliminate the  exacerbation, the appointment of a second antibiotic was required. Conclusions. The results obtained make it possible to recommend the Raman spectroscopy method for determining the sensitivity of microflora to antibiotics, as highly informative in clinical practice.